EFFECT OF (CH2)N ON CHARACTERISTICS ORGANIC THE WASTE PELLET FUEL - Pudji Muljanto, Widodo; Mustiadi , Lalu; Ardi Widodo , Kartiko (Journal of Sustainable Technology and Applied Science (JSTAS), 2023)
The effect of (CH2)n on the combustion characteristics of organic waste pellet fuel has been studied visually and experimentally at atmospheric pressure and temperature in the experimental room. Organic waste particles contain (C, O, Mg, Al, Si, Ca) and plastic bottle oil formed as polyethene (CH2)n. Based on the percentage mass ratio (1, 5, or 10 %), pellet fuel is made from polyethene and organic waste charcoal particles. The burning characteristics of the pellets were identified from the time and temperature signals of the flame by ignition of a shot under the junction of the thermocouple. The faster love starting time and increasing rate of pellet burning were indicators of the results, which demonstrated that the larger the mass of the mixture, the more significant the effect on the pellet burning process. The catalyst in organic waste charcoal binds hydrogen from (CH2)n, forming a weak molecular structure (CH2)n with a low density so that it quickly evaporates and burns. As the mass of the mixture increases, the moles of carbon in the pellets increase. So, the more critical the mass ratio of the mix, the more important the energy absorption property becomes. This creates a stoichiometric reaction equilibrium by making the combustion energy release rate go up. The increasing mass of the mixture helps generate more incredible activation energy in burning organic waste charcoal pellets, confirmed by the more excellent absorption of infrared %T energy.